Scutellaria baicalensis georgi is a promising candidate for the treatment of autoimmune diseases - Wang, Jun; Chen, Shanshan; Zhang, Jizhou; Wu, Jiasi (Frontiers in Pharmacology, 2022)
Autoimmune diseases a group of disorders elicited by unexpected outcome of lymphocytes self-tolerance failure, and the common members of which include multiple sclerosis, systemic lupus erythematosus, inflammatory bowel disease, rheumatoid arthritis, and type 1 diabetes mellitus, etc. The pathogenesis of autoimmune diseases is not fully understood and the current therapeutic regimen’s inefficacy in certain cases coupled with low rates of success, exorbitant financial burden, as well as numerous side effects, which do open new avenues for the role of natural products as novel therapeutic agents for auto-inﬂammatory disorders. Scutellaria baicalensis Georgi is a well-known and widely-recognized herbal medicine with certain ameliorative effect on diverse inflammation-involved dysfunction. Though recent advances do highlight its potential to be applied in the fight against autoimmune diseases, the specific mechanism and the related opinion on the exploring possibility are still limited which hampered the further progress. Here in this timeline review, we traced and collected the evidence of how Scutellaria baicalensis Georgi and its bioactive contents, namely baicalin, baicalein, wogonoside and wogonin affect autoimmune diseases. Moreover, we also discussed the clinical implications and therapeutic potential of Scutellaria baicalensis Georgi and its bioactive contents in autoimmune diseases treatment.